Desain Antena Mikrostrip Rectangular Frekuensi 3,5 GHz Menggunakan Metode Slits - Shinta Romadhona; M. Panji Kusuma Praja; Raditya Artha Rochmanto (Science Tech: Jurnal Ilmu Pengetahuan dan Teknologi, 2023)
In the frequency spectrum of 5G technology, there are three sub-frequencies, namely low band, midband, and high band. For the midband frequency, such as 3.5 GHz, it requires high data speed and wide coverage to support Enhanced Mobile Broadband (eMBB) services with high quality. Therefore, antennas are needed to meet the transmitter and receiver requirements for the 3.5 GHz operating frequency. An antenna with small dimensions is necessary to be used in limited spaces, thus a rectangular microstrip antenna with slit method is designed. For this research, it is limited to simulations using HFSS 15 to find the maximum possible optimization values by adjusting patch dimensions, substrate, and strip line. The return loss result at the operating frequency of 3.5 GHz is -20.0202 dB, and the VSWR is 1.2216. The final step is to add the slit method, which aims to improve the return loss, VSWR, and reduce the antenna dimensions. The optimization result with the slit method is achieved with a patch width of 25.43 mm and a patch length of 19.67 mm. The VSWR value decreases by 0.0701, indicating improved performance. The magnitude gain of the antenna is 3.8253 dB at a theta angle of 360 degrees.